PENGARUH GREEN ACCOUNTING DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Arneta, Cindy; Susanti, Apit (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research aims to determine the influence of the independent variables, namely green accounting, environmental performance, company size, profitability, capital structure and company growth on the dependent variable, namely company value in consumer non-cyclicals and basic materials sub-sector companies that are consistently listed on the Indonesia Stock Exchange (BEI). during the period 2020 to 2022. This research used a purposive sampling method with results from 38 companies in the consumer non-cyclicals, customer cyclicals and basic materials sub-sectors listed on the Indonesia Stock Exchange (BEI) during the period 2020 to 2022 with a total of 112 company data after outliers. This research uses a multiple regression model as a data analysis method. The results in this study show that the profitability variable has a positive effect on company value, which means that the higher the profitability, the higher the company value will be and the company growth variable has a negative effect on company value, which means that the more company growth increases, the company value will decrease. Meanwhile, green accounting variables, environmental performance, company size and capital structure have no effect on company value.